The effects of Covid-19 on roadrunners in Cape Town - Gani, Usraa (Division of Emergency Medicine, 2025)
Background During the worldwide pandemic declared at the beginning of 2020, many people and organisations were affected by the consequences of COVID-19 as well as the infection itself. Due to high transmission rates, strategies were in place to reduce the spread of the virus. While physical activity is well-known to prevent the adverse effects of COVID-19, it was difficult to maintain this behaviour during the COVID-19 lockdown. It takes four weeks of cessation of activity to note a decline in cardiovascular and neuromuscular adaptations. Aim The aim of the study was to explore the effects of COVID-19 infection and Post-Acute Sequelae of COVID-19 (PASC) on the athletic performance of long-distance roadrunners in the Cape Town Metropolitan area. Method A descriptive cross-sectional survey was conducted among roadrunners recruited from athletic clubs in the Cape Town Metropole. Instruments included a self-developed questionnaire exploring COVID-19 infection and PASC. The questionnaire included symptoms of COVID-19 and PASC, the history of the runners' pre-COVID running parameters, the runners' parameters two weeks post-COVID and four weeks post-COVID. Results Fifty-three out of seventy-six participants reported to have tested positive for COVID-19, and twenty-six of these participants experienced PASC (long COVID) symptoms. The most common symptoms of COVID-19 and PASC were fever and headaches for COVID-19 (53.8%) and fatigue for PASC (73.1%). There is a noted increase in heart rate (p < 0.00001) and race pace (p < 0.05) at two weeks and four weeks post-infection (p < 0.00001). It has taken more than three months to return to pre-COVID parameters in 22 participants, with fatigue being the most common symptom and shortness of breath being the second most common symptom affecting return to running. Discussion A significant decline in a proxy measure of performance parameters was noted in the 5 km time trial, RPE measures, race pace, and resting heart rate from the results. The symptoms runners experienced were noted in research by other studies and are taken as the common symptoms affecting return to life and sport. This study has the potential to be taken forward on a bigger scale to provide a generalisation of the results to the public. Conclusion COVID-19 is clearly a multi-factorial systemic infection that has a wide range of symptoms. However, specific symptoms of the infection have lasting effects on the population. The effect on the sporting world is still to be explored with new data and factors to consider within the field.